THE IMPLEMENTATION OF CODE MIXING AND CODE SWITCHING IN EFL CLASS - Emita Dwisda Rakhmannia (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2022)
Language plays a crucial role in communication. English is regarded as a foreign language and is a required subject, particularly in Indonesian secondary schools. Every citizen spoke at least two languages, namely their mother tongue or regional language (B1) and Indonesian (B2). Despite the fact that they also use mother tongue or regional language in daily life to express respect and familiarity with interlocutors from the same group, Indonesian is typically used in both formal and informal contexts. This means that Indonesian students have limited exposure to English because English is only used in formal contexts and is rarely used outside the classroom. In language classrooms, code-switching is a strategy used to facilitate conversation. However, code-switching and code-mixing can help students improve their English speaking skills. The purpose of this study was to investigate how teachers and students implement code switching or mixing in EFL classrooms. This research method employs qualitative research by describing and identifying patterns directly associated with particular phenomena. The outcome demonstrated that code switching or code mixing in EFL classrooms can be an effective educational strategy.